The Historical and Cultural Heritage of the Silk Road: Urgent Issues and Research Prospects - Karimjonova Shahlo Ravshanjonovna (Jurnal Multidisiplin Madani, 2024)
The Silk Road, as an ancient network of trade routes, played a critical role in fostering economic, cultural, and social exchanges between East and West. The historical and cultural legacy of the Silk Road has continued to be a subject of academic interest, offering rich insights into cross-cultural interactions, technological transfers, and the spread of religions and ideas. This paper explores the significance of the Silk Road’s heritage, current challenges in preserving its legacy, and the prospects for future research, focusing on the intersection of history, archaeology, and cultural preservation